The Training and Mentoring in The Preparation of RPJMD Based on Pro-Poverty and Gender Equality in Kubu Karangasem Village, Bali - Bandiyah Bandiyah (Institute for Research and Community Services, 2018)
The training activities of Medium Term Village Program Plan (RPJMD) were conducted based on some problems of poverty and gender faced by the inhabitants of Kubu Karangasem Village. This training aimed to provide the capacity building in technical writing, elaborating, and analyzing of development planning problems faced by the village. In addition, it helped to alleviate the task of central and local government officials in producing good-quality RPJMD output by using the pro-poverty approach and gender equality as an effort of commitment by all parties in planning, budgeting, implementing, monitoring and evaluation of policy. The methods of activity used were training and mentoring in the preparation of RPJMD. The results of this activity showed that first the Kubu Village government officials were able to determine poverty indicators and conduct alternative analysis to solve the poverty problems faced by the inhabitants of the village. Second, the Kubu Village government officials were able to determine development planning budgets for women and children and also encourage women's involvement in planning and activities. Overall, the community-service activities succeeded in providing the knowledge and skills to facilitate the preparation of the RPJMD.